Organizational Factors Contributing To Service Recovery Performance In Indonesian Islamic Banks - Dalimunthe, Zainul Bahri (2014)
This study investigated the organizational factors contributing to service recovery performance in Indonesian Islamic Banks by using management commitment to service quality and employee knowledge sharing capabilities as predictors. The role of perceived organizational support as a moderator between the two above mentioned predictors and the service recovery performance in Indonesian Islamic Banks was also investigated. The sample of this study was frontline employees of Indonesian Islamic Banks, and data were collected through mail survey using questionnaires. The results of this study found that two dimensions of management commitment to service quality (training and rewards) positively and significantly influenced service recovery performance of frontline employee. Empowerment did not significantly influence service recovery performance of frontline employee. The present study also found that all dimensions of employee knowledge sharing capabilities positively and significantly influenced the service recovery performance of frontline employee. The results of this study show that perceived organizational support did not significantly moderate the influence of dimensions of two predictors on service recovery performance. However, perceived organizational support moderate the influence of tacit knowledge-sharing capabilities on service recovery performance of frontline employee. None of the control variables significantly influence statistically the service recovery performance of frontline employee except educational qualifications. The study also provides discussion on the findings as well as limitations, theoretical and practical implications of the study, and suggestions for future research.